Coverage Effects and the Nature of the Metal−Sulfur Bond in S/Au(111): High-Resolution Photoemission and Density-Functional Studies - Rodriguez, José A; Dvorak, Joseph; Jirsak, Tomas; Liu, Gang; Hrbek, Jan; Aray, Yosslen; González, Carlos (Journal of the American Chemical Society, 2003)
The bonding of sulfur to surfaces of gold is an important subject in several areas of chemistry, physics, and materials science. Synchrotron-based high-resolution photoemission and first-principles density-functional (DF) slab calculations were used to study the interaction of sulfur with a well-defined Au(111) surface and polycrystalline gold. Our experimental and theoretical results show a complex behavior for the sulfur/Au(111) interface as a function of coverage and temperature. At small sulfur coverages, the adsorption of S on fcc hollow sites of the gold substrate is energetically more favorable than adsorption on bridge or a-top sites. Under these conditions, S behaves as a weak electron acceptor but substantially reduces the density-of-states that gold exhibits near the Fermi edge. As the sulfur coverage increases, there is a weakening of the Au−S bonds (with a simultaneous reduction in the Au → S charge transfer and a modification in the S sp hybridization) that facilitates changes in adsorption site and eventually leads to S−S bonding. At sulfur coverages above 0.4 ML, S2 and not atomic S is the more stable species on the gold surface. Formation of S n (n > 2) species occurs at sulfur coverages higher than a monolayer. Very similar trends were observed for the adsorption of sulfur on polycrystalline surfaces of gold. The S atoms bonded to Au(111) display a unique mobility/reactivity not seen on surfaces of early or late transition metals.